Production and characterization of electrospun silk fibroin based asymmetric membranes for wound dressing applications - Miguel, Sónia Alexandra Pereira (2018)
Nowadays, wound dressings with improved properties are under development and among them, asymmetric membranes have gained an increasing interest due to their two-layered structure that mimic both the epidermis and dermis layers of the skin. Herein, a new asymmetric membrane was produced using the electrospinning technique. The top layer was produced with silk fibroin (SF) and poly(caprolactone) to reproduce the dense nature and waterproof ability of the epidermis. On the other hand, the dermis-like bottom layer was manufactured with SF and hyaluronic acid loaded with an herbal drug (thymol (THY)). All the data gathered showed that the produced electrospun asymmetric membrane exhibited the porosity, wettability, and mechanical properties suitable for the healing process. Further, the in vitro data also demonstrated that the human fibroblast is able to adhere and spread at the membranes' surface, thus confirming their biocompatibility. Moreover, the incorporation of THY into the bottom layer of the membrane, improved its antioxidant and antibacterial properties. Overall, the obtained results demonstrate the appropriateness of the produced membrane for wound healing applications.